Innovative chest physiotherapy techniques (the MetaNeb® System) in the intubated child with extensive burns. (2017) - Ferguson, Alexandra; Wright, Sarah
Abstract: Introduction: The Metaneb ® is a new generation Intrapulmonary Percussive Ventilation device utilised by the physiotherapist to assist airway clearance by providing calibrated oscillations during inspiration up to 3.8Hz. Predominantly used in the adult chronic respiratory patient, with anecdotal evidence in intubated patients, it was also proven to be safe in a paediatric lung model lab study. This case report outlines the first use of the Metaneb ® with an intubated child in Australia. The 8 year old patient was retrieved to Lady Cilento Children's Hospital with 61% total body surface area flame burns. The child was difficult to ventilate, immobile, and had retained secretions. The chest x-ray (CXR) demonstrated multifocal regions of atelectasis. Study objectives: To report safe and effective use of the Metaneb ® airway clearance in the paediatric intubated patient. Methods: The Metaneb ® was applied using an open ended bagging circuit on Continuous High Frequency Oscillation mode for a period of 10 min per treatment. The circuit contained an inline nebuliser containing 5ml 0.9% normal saline. PEEP was maintained and variable volume breaths were delivered with suction performed as required. Outcome variables to be measured included sputum weight and quality, CXR, and Peak Inspiratory Pressure (PIP) values pre and post treatment. Vital signs were monitored throughout. Results: The patient's vital signs remained stable throughout intervention. After 4 days of treatment twice daily, there was resolution of focal changes on CXR, improvement in secretions, a reduction in PIP and the patient was extubated. Conclusion: The Metaneb ® was used safely and effectively in this patient to assist in resolution of respiratory pathology. Metaneb ® provided a new option for physiotherapy treatment when positioning and handling restrictions limited usual care. This ultimately optimised PICU Length of stay and patient morbidity and mortality. Metaneb ® provided by Hill-Rom Australia.